2009
DOI: 10.4321/s0213-61632009000400004
|View full text |Cite
|
Sign up to set email alerts
|

Delusions of Pregnancy with Post-Partum Onset: An Integrated, Individualized View

Abstract: -Background and Objectives: Bizarre hypochondriacal delusion is an important content of delusion of pregnancy during post-partum period.Methods: Here we report two cases with postpartum delusion of pregnancy; one with pre-existing schizophrenia and another one with family history of pseudocyesis and schizoaffective disorder but with no pre-existing psychiatric illness.Results: Nosological, phenomenological and aetiological issues are discussed. In the context of novel deficit-and motivational theories of delus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…It is seen in subjects of either gender. [6] It is suggested that delusional belief of being pregnant in females is usually labeled as “pseudocyesis” because of presence of physical signs and symptoms related to pregnancy accompanying the belief. In a review of literature, some authors have suggested that there are certain similarities and differences between delusions of pregnancy and pseudocyesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is seen in subjects of either gender. [6] It is suggested that delusional belief of being pregnant in females is usually labeled as “pseudocyesis” because of presence of physical signs and symptoms related to pregnancy accompanying the belief. In a review of literature, some authors have suggested that there are certain similarities and differences between delusions of pregnancy and pseudocyesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this state, the behavior of the male resembles a pregnant woman, although he knows that he is not pregnant. [6]…”
Section: Discussionmentioning
confidence: 99%
“…This Psychopathology is uncommon, though reported in various psychiatric disorders such as schizophrenia, schizo-affective disorders,[ 1 2 3 4 ] delusion disorders and[ 5 6 ] affective disorders. [ 7 ] However, these symptoms are also reported in organic disorders such as epilepsy,[ 8 9 ] in dementia, and other organic brain syndromes[ 10 11 ] as well as in medical conditions such as drug-induced lactation,[ 12 ] polydipsia and hyponatremia syndrome,[ 13 ] and antipsychotic-induced hyperprolactinemia. [ 14 ] Delusion of pregnancy has not only limited to female but also reported in males.…”
Section: Introductionmentioning
confidence: 99%
“…The mother establishes an undisturbed union with her fetus during pregnancy, which eliminate loneliness and helplessness in a magical way that can serve as a basis for delusion formation. [ 10 ] Similarly, loss of love and loss of a loved object (or of fertility), acute loneliness, and real/imagined loss of relationship were hypothesized to activate a delusion of pregnancy on a wish-fulfilling manner. [ 15 16 ] Some unusual cases have also been published, for example, recurrent delusion of pregnancy,[ 17 ] experience of labor and parturition,[ 18 ] puppy pregnancy in humans,[ 19 ] delusion of test-tube pregnancies,[ 20 ] and delusional pregnancy persisting over decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation